P295 Establishing adenosine deaminase 2 activity in a cohort of patients with large vessel vasculitis. (23rd April 2022) - Porter, Andrew; Maughan, Robert; Pericleous, Charis; Kiprianos, Allan; Jee, Hyuk; Lee, Pui; Youngstein, Taryn; Mason, Justin
Abstract: Background/Aims: Deficiency of adenosine deaminase 2 (DADA2) leads to a broad phenotype; some patients develope vasculitis and strokes, and others have predominantly haematological manifestations. Small, medium and large vessel vasculitis has been described. In contrast, plasma ADA2 activity is elevated in inflammatory conditions including systemic lupus erythematosus and systemic juvenile idiopathic arthritis with macrophage activation syndrome. The role of ADA2 and how its deficiency associates with the vasculitides is not well understood. Using a well-characterised large vessel vasculitis cohort, we sought to establish the potential role of ADA2 activity. Methods: ADA2 activity was measured in adults with Takayasu arteritis (TA), large vessel giant cell arteritis (LV-GCA), intracranial vasculitis (IV) and healthy control (HC) subjects using a coupled spectrophotometric assay. Plasma from 11 patients with genotyped DADA2 and 10 patients heterozygous for pathogenic variants in ADA2 were used to define thresholds for deficiency and carrier status respectively (DADA2 activity 0 - 0.90 U/L, ADA2 carrier activity 2.02 - 10.62 U/L). Activity levels above the upper limit of normal (ULN) were defined as > 99th percentile of the HC activity (30.3U/L). To assess potential associations with TA disease status, ADA2 was measured prospectively in matched active and remission samples. TA disease activity was determined as active, grumbling or stable using clinical and radiological features, physician impression, CRP, ESR and Indian Takayasu clinical Activity Score (ITAS). Results: No patients had deficient ADA2 activity while 7 subjects had activity within the carrier range (1 HC [1.9%], 5 TA [3.7%], 1 LV-GCA [2.3%]). Compared to HC levels (17.43 [14.11 - 20.78] U/L), activity in the TA group was significantly increased (TA 19.68U/L, p = 0.0061), while LV-GCA and IV were not significantly different. In 20 cases, activity exceeded the ULN; 16 TA (11.9%, p = 0.044; 4 active, 2 grumbling, 10 stable) and 4 LV-GCA (9.1%, ns). In TA, there was a positive correlation between ADA2 activity and ESR (Spearman R = 0.2863, p = 0.0009) but not with CRP or ITAS score. Subgroup analysis revealed ADA2 activity was most prominently elevated in the stable group relative to HCs (TA stable 20.54 U/L [8.08 - 48.66], median +17.8%, p = 0.0006), but not with active or grumbling disease. Consistent with this, prospective analysis demonstrated a significant increase in ADA2 activity in remission vs active disease (p = 0.024), with activity increasing in 18 (62%) patients achieving remission. Conclusion: There were no cases of ADA2 deficiency in this cohort. Consistent with other inflammatory conditions, ADA2 activity was elevated in TA compared to HC subjects. Surprisingly, increased ADA2 activity was linked to stable TA in both cross-sectional and prospective analyses. This may suggest a potential role of ADA2 enzyme activity in vascular repair and regrowth - possibly tying in with known elevated levels of ADA2 activity in growing children. Disclosure: A. Porter: None. R. Maughan: None. C. Pericleous: None. A. Kiprianos: None. H. Jee: None. P. Lee: None. T. Youngstein: None. J. Mason: None.